Augmented Expression of NOGO-A and Its Receptors in Human Retinal Pigment Epithelial Cells Following Treatment with Human Amniotic Fluid - Bahar Safdari; Mozhgan Rezaei-Kanavi; Mohammad Amir Mishan; Hamid Ahmadieh; Zahra-soheila Soheili; Iman Slahshouri Far; Fatemeh Suri (Tehran University of Medical Sciences, 2022)
Background: Nogo-A, a myelin-associated inhibitor for neurite outgrowth, has important role in visual system development. Trans-differentiation ability of human amniotic fluid (HAF) on human retinal pigment epithelial cells (hRPEs) towards neural progenitor cells has been observed in several studies. We aimed to investigate the expression of NOGO-A gene and its receptors as a marker of neural differentiation in HAF-treated hRPE cells. Methods: hRPE cells were cultivated and immune characterized via RPE65 and cytokeratin 8/18 protein markers. Also, the cytotoxicity effect of 30% HAF on hRPE cells was evaluated using ELISA cell death assay. Finally, expression of NOGO-A and its receptors, RTN4R and LINGO1 was evaluated in the cells treated with HAF in comparison with FBS-treated cells using quantitative real-time PCR. Results: Harvested cells showed immunoreactivity for cytokeratin 8/18 and RPE65, confirming the hRPE cell identity. Besides, HAF had no cytotoxic effect on hRPE cells compared with FBS-treated cells. Results showed that NOGO-A and its receptors were expressed in cultured hRPE cells. Besides, comparative gene expression analysis revealed significant increased expression of the investigated genes in HAF-treated hRPE cells compared to FBS-treated cells. Conclusion: Augmented expression of NOGO-A and its receptors can support neural differentiation of hRPE when the cells are treated with HAF. Our outcomes provide more evidences on the trans-differentiation ability of HAF on hRPE cells into neural progenitors and retinal neural cells, but further studies are needed to elucidate the exact mechanism.